Eloquent JavaScript: A Modern Introduction to Programming - Haverbeke, Marijn (No Starch Press, Incorporated, 2014)
JavaScript lies at the heart of almost every modern web application, from social apps to the newest browser-based games. Though simple for beginners to pick up and play with, JavaScript is a flexible, complex language that you can use to build full-scale applications.Eloquent JavaScript, 2nd Edition dives deep into the JavaScript language to show you how to write beautiful, effective code. Author Marijn Haverbeke immerses you in example code from the start, while exercises and full-chapter projects give you hands-on experience with writing your own programs. As you build projects such as an artificial life simulation, a simple programming language, and a paint program, youll learn:The essential elements of programming, including syntax, control, and dataHow to organize and clarify your code with object-oriented and functional programming techniquesHow to script the browser and make basic web applicationsHow to use the DOM effectively to interact with browsersHow to harness Node.js to build servers and utilitiesThis edition is thoroughly revised and modernized to reflect the current state of JavaScript and web browsers, with brand-new material, such as a chapter on code performance in JavaScript, and expanded coverage of recursion and closures. All source code is available online in an interactive sandbox, where you can edit the code, run it, and see its output instantly.Isnt it time you became fluent in the language of the Web?.